Human immunodeficiency virus infected patient with decreased of consciousness, what do we think? - Kunti, Desak Putu Sukasanti Adi; Suryana, Ketut (International Journal of Advances in Medicine, 2024)
Central nervous system (CNS) disorders are estimated to occur in approximately 10-20% of people living with human immunodeficiency virus (HIV). Neurological manifestations in HIV-infected patients can be caused directly by HIV or by opportunistic infections. Here we present a case report of a 47-year-old male initially diagnosed with decreased of consciousness in HIV-infected patients on ARV. Differential diagnosis of HIV-infected patients with decreased consciousness must be made. We can consider causes of opportunistic infections such as toxoplasma encephalitis, HIV encephalitis, or both.